Manipulação na telepolítica paraibana: um estudo de caso sobre o último debate entre os candidatos ao governo do estado em 2006 - Camara, Alexandre Jose Barbosa da (2011)
The complex relationship that involves the fields of communication and politics, having as backdrop the search for power, has found in the technology and media modernization, the propitious environment to its growth. There were several changes in postmodern society that passed to dispose of the media space, especially the broadcast media, mainly the television, as a fundamental source of information, entertainment and visibility. Being aware about the media possibilities, the political actor has developed a strategic game based on spectacle and administration of his visibility, acting and spreading from that huge media stage, archetypal images carefully constructed. So, this study aims to analyze the politic spectacle phenomenon in Paraiba State broadcasting, reflecting about the Cabo Branco TV stance in one of the most heated political disputes of Paraiba State that culminated with Cassio Cunha Lima victory. Therefore, this work starts of an interdisciplinary approach and analyzes the final debate video among the candidates for governor of Paraiba, in the 2006 elections. The study is based on communication, sociology and politics theories and studies of the collective imaginary. Complementing this exhibition, there are some newspapers stories published by O Norte newspaper, as well as articles of the Brazilian Electoral Law, whose attempt to regulate the actions of the media have been a constant throughout the history of elections in Brazil. Thus, we seek in the theoretical framework proposed bring out clarifications about the possibility of a strategic use of image, verbal and manipulative conduct in 2006 s debate. So, it is questioned about this broadcast the intention to manage differently, the two government candidates visibility in that year on a space delimitated by audiovisual field.